(3eNGWQ GdESJKeGQ aj GdeUGQa GdGSdGejIs - (3MeRI YHO GdcQje(B, (3eMeO MeGOs ((3YeGf(B:s (3GdfaGFS(B,s, 2008)
(3eNGWQ GdGSJKeGQ aj GdeUGQa GdGSdGejI (B: (3eaghegG , eUGOQgG h BKGQgG h eNGWQ GdGSJKeGQ aj GdeVGQHI h GdeTGQcI h aj GdeQGLYI , eNGWQ GdGSJKeGQ aj GdGSJUfGY h GdSde h HYV GdUjZ GdGNQi eY hLhO HYV GdhSGFd GdeUQajI dJbdjd eNGWQ GdGSJKeGQ aj GdeUGQa GdGSdGejI (B.s
Keywords: (3GdEbJUGO GdESdGejs; (3GdGSJKeGQs; (3GdHfhc GdGSdGejIs